Toll-Like Receptor 4 Is Involved in Inflammatory and Joint Destructive Pathways in Collagen-Induced Arthritis in DBA1J Mice - Pierer, Matthias; Wagner, Ulf; Rossol, Manuela; Ibrahim, Saleh (PLOS ONE, 2011)
In rheumatoid arthritis, a significant proportion of cytokine and chemokine synthesis is attributed to innate immune mechanisms. TLR4 is a prominent innate receptor since several endogenous ligands known to activate the innate immune system bind to it and may thereby promote joint inflammation. We generated TLR4 deficient DBA1J mice by backcrossing the TLR4 mutation present in C3H/HeJ strain onto the DBA1J strain and investigated the course of collagen-induced arthritis in TLR4 deficient mice in comparison to wild type littermates. The incidence of collagen- induced arthritis was significantly lower in TLR4 deficient compared to wild type mice (59 percent vs. 100 percent). The severity of arthritis was reduced in the TLR4 deficient mice compared to wild type littermates (mean maximum score 2,54 vs. 6,25). Mice deficient for TLR4 were virtually protected from cartilage destruction, and infiltration of inflammatory cells was reduced compared to wt mice. In parallel to the decreased clinical severity, lower anti-CCP antibody concentrations and lower IL-17 concentrations were found in the TLR4 deficient mice. The study further supports the role of TLR4 in the propagation of joint inflammation and destruction. Moreover, since deficiency in TLR4 led to decreased IL-17 and anti-CCP antibody production, the results indicate a link between TLR4 stimulation and the adaptive autoimmune response. This mechanism might be relevant in human rheumatoid arthritis, possibly in response to activating endogenous ligands in the affected joints.